Study of Student Perceptions on the Performance, Transparency, and Independence of Bawaslu as the Electoral Supervisory Agency s 2024 - Rasyadi Kuncoro Aji; Muhammad Ridhwan (Universitas Muhammadiyah Ponorogo, 2026)
General elections are one of the main pillars of a democratic system, serving to legitimize power through a peaceful and periodic process. In their implementation, the Election Supervisory Agency (Bawaslu) plays a central role as the supervisory body responsible for ensuring that elections are conducted in a direct, public, free, confidential, honest, and fair manner. This study aims to analyze students' perceptions of Bawaslu's performance, transparency, and independence in the implementation of the 2024 General Election. This study uses a qualitative descriptive method with data collection techniques in the form of a closed Likert scale questionnaire distributed to students at the University of 17 Agustus 1945 Jakarta. The data obtained was analyzed using a descriptive approach based on the frequency distribution and percentage of respondents' answers for each indicator. The results show that the majority of students have a positive perception of Bawaslu's performance and transparency, with a total of 60% and 59.9% of respondents agreeing and strongly agreeing. However, perceptions of Bawaslu's independence tended to be lower, with only 49.4% of respondents agreeing and strongly agreeing, and 50.6% remaining neutral or disagreeing. This shows that although trust in Bawaslu is generally quite good, there are still doubts among students regarding the institution's neutrality from political intervention. This study emphasizes the importance of increasing information transparency, strengthening public communication, and protecting the institutional independence of Bawaslu as part of efforts to strengthen the legitimacy and quality of electoral democracy in Indonesia. The perceptions of students as young voters and a critical group are important indicators in measuring the success of election monitoring functions in the public eye. However, the weakness of this study is the limited number of respondents from one university and the use of a closed questionnaire as an instrument. Future research should involve respondents from various universities and combine quantitative methods with interviews or focus group discussions (FGDs) to obtain a more in-depth and representative picture. Keywords: Bawaslu; Perception; Election;